Hemoglobin Concentration and Post-Operative Delirium in Elderly Patients Undergoing Femoral Neck Fracture Surgery - Liu, Yu-Mei; Huang, Hui; Gao, Jie; Zhou, Jian; Chu, Hai-Chen (Frontiers in Medicine, 2022)
This study aimed to determine the relationship between hemoglobin (Hb) concentration and postoperative delirium (POD) in elderly patients undergoing femoral neck fracture (FNF) surgery, and to investigate whether the change in Hb concentration is associated with POD and the risk factors for POD. A total of 889 patients admitted with FNF between January 2016 and December 2020 were enrolled in this single-center, retrospective, case–control study. Hb concentrations were determined at admission and postoperative day 1, and the change in Hb concentration was defined as the absolute value of difference in preoperative and postoperative Hb concentration. POD was assessed using the Confusion Assessment Method in the Intensive Care Unit or Confusion Assessment Method once a daily after surgery. Logistic regression analysis was performed for statistical analysis. In total, 172 (19.3%) patients developed POD, and 151 (87.8%) developed POD within postoperative 3 days. Low preoperative Hb concentration (P = 0.026, odds ratio [OR] = 0.978) and significant change in Hb concentration (P = 0.006, OR = 1.033) were significantly associated with POD. After excluding change in Hb concentration or preoperative Hb concentration, neither of them was significantly associated with POD. The interaction analysis of change in Hb concentration and preoperative Hb concentration in logistic regression model was negative (P＞0.05). There was no significant relationship between postoperative Hb concentration and POD. age (P < 0.001, OR = 1.072), stroke history (P = 0.003, OR = 2.489), postoperative ICU transfer (P = 0.007, OR = 1.981), and visual analog scale score within postoperative 2 days (P1 = 0.016 and P2 = 0.006) were independently associated with POD in logistic regression analysis. Patients with low preoperative Hb concentrations and high changes in Hb concentration seem to have an increased risk of POD and should receive more attention. Old age, stroke history, postoperative ICU transfer, and pain within postoperative 2 days were significantly associated with POD.